Bariatric surgery and exercise: A pilot study on postural stability in obese individuals - Cibulková, Natálie; Daďová, Klára; Mašková, Kateřina; Busch, Andrew; Kobesová, Alena; Vařeková, Jitka; Hašpicová, Marcela; Matoulek, Martin (PLoS One, 2022)
This study aimed to analyze the changes in postural stability of individuals with obesity after bariatric surgery, and the effect of three months of regular exercise on the static postural stability. Twenty-two subjects (7 females and 15 males) aged 31 to 68 years (Body mass index 35-55 kg.m-2) completed the study. Participants were divided into two groups: one group participated in an exercise program after the bariatric surgery (n = 10; age 48.9 ± 7.5 years; Body mass index 42 ± 5.6 kg.m-2) while the second group did not exercise at all after bariatric surgery (n = 12; age 44.7 ± 13.6 years, Body mass index 42.6 ± 6.0 kg.m-2). Static postural stability was measured using a Tekscan MobileMat pressure plate before and 4 months after the bariatric surgery. The exercise program included exercising three times a week including: one hour of strengthening, one hour of aerobic group exercise and at least one session of individual exercise at home. There were no significant differences in Center of force sway, Center of force ranges and average speed before and 4 months after bariatric surgery. Also, no effect of exercise was found. Post-pre differences of some parameters were negatively related to age (r from-0.46 to-0.72). Further studies are needed to explore this topic in depth.
Keywords: dospělí; Female; techniky fyzikální terapie; Obesity, Morbid; Bariatric Surgery; Adult; Quality of Life; ženské pohlaví; Obesity; kvalita života; lidé; cvičení; Physical Therapy Modalities; Pilot Projects; Exercise Therapy; Postural Balance; pilotní projekty; Weight Loss; obezita; Male; Aged; bariatrická chirurgie; index tělesné hmotnosti; hmotnostní úbytek; terapie cvičením; lidé středního věku; senioři; mužské pohlaví; Body Mass Index; Exercise; Middle Aged; morbidní obezita; posturální rovnováha; Humans